Use of digital imaging for gradation and breakage of railway ballast - Gaitskell, P.; Shahin, Mohamed (The Australian Geomechanics Society, 2013)
The foundation of ballasted railway is usually consisted of a graded layer of granular media of ballast placed above naturally deposited subgrade. The ballast layer is responsible for limiting the vertical stress magnitudes applied to the weaker subgrade and also prevents the vertical and lateral train-induced sleeper movements. In recent years, the progressive use of faster and heavier trains has compromised the ability of ballast to resist such movements due to the increased magnitude of ballast breakage (degradation). Therefore, accurate determination of ballast breakage is important. The amount of ballast breakage can be estimated by comparing the gradation (particle size distribution) curves of fresh and degraded ballast, using a ballast breakage index. However, the Australian railway authorities currently rely on the visual inspection for estimating ballast breakage. Despite the fact that the visual inspection is convenient, as it does not require transport of ballast samples or testing, it is subjective and can lead to uneconomical maintenance cycles. In this paper, an attempt is made to utilise the digital imaging technique for gradation analysis and breakage estimation of ballast. The technique is fast and convenient, and can be applied to both the laboratory and field conditions, hence, can be used successfully to replace the visual inspection of ballast breakage.